A governação "sombra" no espaço marítimo angolano - Bentral, Francisca Nassoma Kumandala (2021)
The sea is a vital resource for human survival and an engine for the national economy. Angola's interest in extending its continental shelf beyond 200 nautical miles and delimiting the maritime border in the northern part of the country, encourages the creation of an instrument for the planning and management of activities and uses in the national maritime space, in order to affirm an intimate relationship with the sea. We propose the creation of this legal law to eliminate the lack of planning and management of the use and use of human activities that occur in Angolan maritime areas, both in space and in temporal terms, with a view to minimizing conflicts of overlap between ministerial departments with attribution in ocean matters, in order to achieve sustainable governance of marine resources and services. It is intended to accommodate a new vision of our sea, through the governance of its areas involving all public and private sectors with matters related to the sea, based on an articulated ecosystematic approach. The present research work aims to plan, order and manage the different uses, uses and appropriately distribute activities in the maritime area through the planning process with a view to implementing the sectarian policies in these areas. In a context of economic and financial disruption, the value of our ocean waters constitutes a strategic positioning (economic, environmental, scientific research and military) to promote sustainable development, to generate wealth and to affirm the exercise of sovereignty power and jurisdiction of the Angolan State in the maritime space. Angola has one of the world's great marine ecosystems and at sea is immense wealth properly measured, but not exploited or used rationally to achieve sustainable development.